L’Aktionsart dans la construction rougir de colère - Kleiber, Georges (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2022)
We aim to study the Aktionsart or lexical aspect of chromatic verbal expressions such as rougir de colère (blush with anger). The aim is twofold. First, to show that the verb blush in these expressions is not the same as the one that appears in purely chromatic uses such as Les pommes rougissent au soleil (Apples blush in the sun). Secondly, to explain the originality of Aktionsart’s “chromo-affective” use of blush.